The influence of Mg/Al molar ratio on the performance of CuMgAl-x catalysts for CO2 hydrogenation to methanol - Liu, Haoran; Huang, Wenbin; Xu, Zhen; Jia, Yijing; Huang, Meng; Liu, Xiaoyue; Yang, Han; Li, Rongrong; Wei, Qiang; Zhou, Yasong (Frontiers in Chemistry, 2024)
The CuMgAl-x catalysts derived from hydrotalcite precursors with different Mg/Al molar ratios were synthesized and applied to CO2 hydrogenation to methanol reaction. In this study, the effects of Mg/Al molar ratio on the structure and surface properties of CuMgAl-x catalysts were investigated by XRD, N2 adsorption-desorption, SEM, TEM, H2-TPR, CO2-TPD, XPS, and in situ DRIFTS characterization methods. The results showed that an appropriate Mg/Al molar ratio can enhance the Cu-MgO interaction, increasing the basic sites and obtaining suitable acid sites. The dispersion of active Cu on the CuMgAl-x catalysts can be improved by strong Cu-MgO interaction, which enhances the adsorption capacity of CO2 and makes H2 activation easier, accelerates the conversion of intermediate species CO3 * and HCO3 * to HCOO * , and facilitates further conversion to CH3O * and CH3OH. The strong interaction between Cu and MgO was conducive to the formation of Cu + , which can inhibit the desorption of CO in the RWGS reaction. The CuMgAl-3 catalyst showed the highest CO2 Conversion rate(14.3%), methanol selectivity(94.5%), and STY of methanol (419.3 gkgcat. -1 h -1 ) at 240 °C and 2.5 MPa. The results obtained in this paper can provide a new idea for the design of high-performance catalysts for CO2 hydrogenation to methanol.